Perancangan Indikator Kinerja Utama Logistik Menggunakan Pendekatan Balanced Scorecard - Lubis, Ibnu Farras Azzikri; Nabila, Hadisty; Sembiring, Anita Christine (CV. IRA PUBLISHING, 2025)
This study aims to design a logistics performance measurement system at PT. XYZ is using the BSC approach combined with KPIs. The company operates in the field of steam turbine maintenance and repair services for the palm oil industry, but does not yet have a structured logistics performance evaluation system. The study was conducted for six months through interviews, observations, questionnaires, and documentation studies. The evaluation covered four BSC perspectives: financial, customer, internal processes, and learning and growth, with KPI analysis for each perspective. The results show that logistics performance fluctuates, especially in the aspects of customer satisfaction and employee training. A relationship was found between the perspectives, namely that decreased training has an impact on increasing delivery errors. The BSC and KPI approach has been proven to provide a comprehensive picture of logistics performance and is relevant to support strategic management. Recommendations include strategy integration, strengthening training, and improving service quality for sustainable efficiency.